The Higher C-Reactive Protein Levels as a Risk Factor of Stunting in Children with Acyanotic Congenital Heart Disease - Pangestika, Niluh Putu Wida; Putra, I Gusti Ngurah Sanjaya; Sidiartha, I Gusti Lanang; Windiani, I Gusti Ayu Trisna; Gunawijaya, Eka; Mahalini, Dewi Sutriani; Sukmawati, Made (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Children with acyanotic congenital heart disease (CHD) had a high risk of stunting. In addition to inadequate nutrition, chronic inflammatory process also plays an important role. An increase in serum c-reactive protein (CRP) suppresses insulin like growth factor 1 (IGF-1) production, causing disorder in child growth. AIM: The objective f the study was to prove that higher CRP levels as a risk factor of stunting in children with acyanotic CHD aged 6–24 months old. METHODS: This study is an observational analytic study with a case–control design, to assess higher CRP levels as a risk factor of stunting in children with acyanotic CHD aged 6–24 months old. This research was conducted at the Pediatric Cardiology Polyclinic, Sanglah Hospital from May to December 2021 with the consecutive sampling method. Data analysis was performed using the Chi-square test or Fisher’s absolute test. Multivariate analysis with binary logistic regression was performed on all variables. Significance level was p < 0.05. RESULTS: This study involved 60 subjects, consisting of 30 subjects with stunting and 30 subjects with no stunting. Children with stunting had higher mean CRP levels, 2.4 (±3.7) and 1.2 (±0.6). CRP level ≥3 mg/dL (p = 0.031; aOR 22.89; 95% CI 1.32–395.39) was a risk factor of stunting in children with acyanotic CHD. Other risk factors that significant are male, living in rural areas, low birth weight, and under-nutrition. CONCLUSION: Higher CRP levels as a risk factor of stunting in children with acyanotic CHD. Other significant risk factors include males, living in rural areas, low birth weight, and under-nutrition.